Evaluation of the relationship between the biosecurity status, production parameters, herd characteristics and antimicrobial usage in farrow-to-finish pig production in four EU countries. Issue 1 (December 2016) - Postma, Merel; Backhans, Annette; Collineau, Lucie; Loesken, Svenja; Sjölund, Marie; Belloc, Catherine; Emanuelson, Ulf; grosse Beilage, Elisabeth; Nielsen, Elisabeth; Stärk, Katharina; Dewulf, Jeroen
Abstract Background High antimicrobial usage and the threat of antimicrobial resistance highlighted the need for reduced antimicrobial usage in pig production. Prevention of disease however, is necessary to obtain a reduced need for antimicrobial treatment. This study aimed at assessing possible associations between the biosecurity level, antimicrobial usage and farm and production characteristics in order to advice on best practices for a low antimicrobial usage and maximum animal health and production. A cross-sectional study was conducted in 227 farrow-to-finish pig herds in Belgium, France, Germany and Sweden between December 2012 and December 2013. Associations between biosecurity status, antimicrobial usage, and production parameters were evaluated with multivariable general linear models, according to an assumed causal pathway. Results The results showed that higher antimicrobial usage in sows tended to be associated with higher antimicrobial usage from birth until slaughter (p = 0.06). The antimicrobial usage from birth until slaughter was positively associated with the number of pathogens vaccinated against (p < 0.01). A shorter farrowing rhythm (p < 0.01) and a younger weaning age (p = 0.06) tended to be also associated with a higher antimicrobial usage from birth until slaughter whereas a better external biosecurity (p < 0.01) was related with a lower antimicrobial usage from birth until slaughter. Conclusion Management practices such as weaning age and biosecurity measures may be important factors indirectly impacting on antimicrobial usage. We therefore promote a holistic approach when assessing the potential to reduce the need for antimicrobial treatments.